Classifying Disorders of Consciousness: Past, Present, and Future - Kondziella, Daniel; Stevens, Robert D. (Seminars in Neurology, 2022)
With the advent of advanced analytical methods applied to functional neuroimaging and neurophysiological data, cerebral conditions have been defined that challenge the established classification of disorders of consciousness. A subset of brain-damaged patients has been identified who cannot carry out motor commands, but who exhibit patterns of cerebral activation during mental imagery tasks that are indistinguishable from those in healthy controls. This condition, termed “cognitive motor dissociation,” has overturned many assumptions regarding the detection, diagnosis, prognosis, and care of patients with brain injury. Three factors are likely to influence efforts to improve the classification of disorders of consciousness in the near future: the types of data that will become available to characterize brain states, the modeling paradigms utilized for data analysis, and the ability to implement classification schemes in the clinical setting. Here we review past achievements, present states, and future projections for the classification of impaired consciousness and responsiveness.
Keywords: brain injury; coma; consciousness; endotypes; functional MRI; vegetative state; minimal conscious state; unresponsive wakefulness syndrome